A Diáspora Africana, ‘Desenvolvimento’ & Moderna Teoria Política Africana - Adi, Hakim (Revista Direito e Práxis, 2020)
DOI:10.1590/2179-8966/2020/42150 A Diáspora Africana, ‘Desenvolvimento’ & Moderna Teoria Política Africana The African diaspora, ‘development’ & modern African political theory Hakim Adi Universidade de Chichester, Chichester, West Sussex, Reino Unido. E-mail: adi@chi.ac.uk. ORCID: https://orcid.org/0000-0003-4778-9320. Versão original: Hakim Adi (2002) The African diaspora, ‘development’ & modern African political theory, Review of African Political Economy, 29:92, 237-251, DOI: 10.1080/03056240208704611 Tradução Mario Soares Neto, Universidade Federal da Bahia, Salvador, Bahia, Brasil. E-mail: mario.soares@ufba.br, mario.adv.soares@gmail.com